Sperm morphology of Muscidifurax uniraptor (Hymenoptera: Chalcidoidea: Pteromalidae). Issue 3 (May 2016) - Santos, Helen Pinto; Barcellos, Marcelo Silva; Reis, Aline Beatriz; Dolder, Heidi; Lino-Neto, José
Abstract: Sperm morphology of the parasitoid Muscidifurax uniraptor was investigated under light and transmission electron microscopy. M . uniraptor sperm are filiform, spiraled, approximately 150 μm in length, with a distinctive head, hooded by an extracellular sheath and a flagellum. This extracellular layer, from which many filaments radiate, measures approximately 90 nm in thickness and covers a small acrosome and the anterior nuclear region. The acrosome is composed of an acrosomal vesicle and a perforatorium with its base inserted in the nuclear tip. The nucleus is filled with homogeneously compacted chromatin. The centriolar adjunct extends towards the anterior portion in a spiral around the nucleus for 3.5 μm in length. The two mitochondrial derivatives begin exactly at the centriole adjunct base and, in cross-section, have a circular shape with equal areas that are smaller than the axoneme diameter. It is coiled, with 9 + 9 + 2 microtubules and begins from the centriole, just below the nuclear base. The axoneme is connected to the mitochondrial derivatives by two small irregularly shaped masses. Between the derivatives and the axoneme, the 'center-flagellar material' is observed. Overall, these characteristics are recognized in other Chalcidoidea, especially in the eurytomids, but together they form a set of species-specific data. Highlights: The M . uniraptor sperm show a thick extracellular sheath that covers a small acrosome and the anterior nuclear region. The centriolar adjunct extends anteriorly in a spiral around the nucleus for 3.5 μm in length. Among Chalcidoidea, Pteromalidae and Eurytomidae show the closest similarity in sperm morphology.